Characterization of wake interference between two tandem offshore floating vertical-axis wind turbines: Effect of platform pitch motion. (1st August 2022) - Kuang, Limin; Lu, Qi; Huang, Xuan; Song, Leijian; Chen, Yaoran; Su, Jie; Han, Zhaolong; Zhou, Dai; Zhao, Yongsheng; Xu, Yuwang; Liu, Yijie
Highlights: Wake interference between two tandem offshore floating VAWTs is investigated. Effect of platform pitch motion on power and wake of floating turbine array is evaluated. Parametric analysis of effects of varied pitch characteristics is performed. Mechanism of pitch motion alleviating negative effect of wake interference is revealed. Provide a basic reference for designing offshore floating wind farms. Abstract: The wake interference within the offshore wind farms, especially with the tandem arrangement scenario, affects the designed total power output. Also, the six degrees of freedom motions of the platforms not only can change the aerodynamics of the offshore floating wind turbines, but also may influence the wake interference between them. In the present study, the effect of the platform pitch motion on the wake interference between two tandem offshore floating vertical-axis wind turbines (VAWTs) is characterized using the improved delayed detached-eddy simulation (IDDES). First, the power performance of the downstream turbine (VAWT Ⅱ) at different separation distances, 2 D  ≤  LS  ≤ 10 D, and tip speed ratios, 0.4 ≤ TSR Ⅱ ≤ 1.5, are analyzed, assuming that the upstream turbine (VAWT Ⅰ) is bottom-fixed and operates at an optimal TSR Ⅰ of 1.2. Then, the effects of the pitch amplitude, 5° ≤ AP Ⅰ ≤ 15°, and pitch period, 2 T Ⅰ ≤ TP Ⅰ ≤ 8 T Ⅰ, on the wake interference are characterized by assuming that the platform pitch motion of VAWT Ⅰ follows a prescribed simple harmonic law. The results show that locating VAWT Ⅱ in the medium wake region of VAWT Ⅰ, e.g., LS  = 6 D, can appropriately balance the power performance and space cost of the bottom-fixed turbine array. Also, the platform pitch motion can reduce the mean velocity deficit in the core wake region of VAWT Ⅰ. The mean wake deficit reduction increases the averaged power coefficient of VAWT Ⅱ, e.g., up to 22.67% when LS  = 6 D, TSR Ⅱ = 1.2, AP Ⅰ = 15°, and TP Ⅰ = 4 T Ⅰ . In addition, relatively larger pitch amplitudes and smaller pitch periods will further alleviate the negative effect of the wake interference. This study may serve as a reference for designing offshore floating wind farms.